Fungal ITS2 data from Pyroleae and Monotropa hypopitys germination study - Veronika Johansson (Stockholm University, 2026)
This dataset contains ITS metabarcoding data describing fungal communities associated with germinating seeds and early developmental stages of Pyroleae species and Monotropa hypopitys in Sweden. The data were generated using high-throughput sequencing of the ITS2 region to characterize ectomycorrhizal fungal diversity and its relationship to plant development and ecological conditions.DescriptionThe dataset originates from a field-based seed sowing experiment designed to investigate fungal associations during early ontogeny of mycoheterotrophic and partially mycoheterotrophic plants (Johansson et al. 2017). Seed bags were deployed across multiple forest sites and retrieved over multiple years to assess germination, seedling development, and associated fungal communities. DNA was extracted from germinated seedlings and analyzed using ITS metabarcoding of the ITS2 region. The resulting dataset includes operational taxonomic units (OTUs), taxonomic assignments, and sequence read abundances, providing a detailed characterization of fungal diversity associated with early plant life stages.PurposeThe purpose of this dataset is to document the diversity and composition of fungal communities associated with early developmental stages of selected plant species and to support research on plant-fungal interactions, mycoheterotrophy, and forest ecosystem processes, building on the findings presented in Johansson et al. 2017, Mol Ecol, 26: 2591-2604. https://doi.org/10.1111/mec.14050

This dataset was published via the SBDI ASV portal (https://asv-portal.biodiversitydata.se/) .
Keywords: Monotropa hypopitys; metabarcoding; Sweden; Pyroleae; dust seeds; ITS; mycoheterotrophy; Occurrence; ectomycorrhizal fungi; seedling development; fungal communities; OCCURRENCE; Biological Sciences; Biologi